2023
DOI: 10.12681/psy_hps.29862
|View full text |Cite
|
Sign up to set email alerts
|

University students’ mental health and affect during COVID-19 lockdown in Greece: the role of social support and inclusion of others in the self

Aikaterini Vasiou,
Panorea Andriopoulou

Abstract: The aim of the study was to examine the perceived social support and inclusion of others in the self as predictors of students’ mental health and affect during COVID-19 lockdown. One hundred and thirty-seven university students from Greece participated in a cross-sectional study completing a number of self-report online questionnaires such as the General Health Questionnaire, the Job Affect Scale, the Multidimensional Scale of Perceived Social Support and the Inclusion of Others in the Self scale. Results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…We found that for students with higher depression/anxiety levels, the family (not the teacher) was the main source of support. Other studies also revealed family social support as the main protective factor of students' mental health during the pandemic, e.g., [100][101][102]. However, considering that the lack of in-person instruction not only alters the learning environment but also disrupts traditional learning patterns [103], as observed by Bilz [104], we were able to identify that depressed or anxious students are only moderately identified by their teachers because they tend to be silent and/or absent.…”
Section: Discussionmentioning
confidence: 60%
“…We found that for students with higher depression/anxiety levels, the family (not the teacher) was the main source of support. Other studies also revealed family social support as the main protective factor of students' mental health during the pandemic, e.g., [100][101][102]. However, considering that the lack of in-person instruction not only alters the learning environment but also disrupts traditional learning patterns [103], as observed by Bilz [104], we were able to identify that depressed or anxious students are only moderately identified by their teachers because they tend to be silent and/or absent.…”
Section: Discussionmentioning
confidence: 60%